Pengaruh penambahan tepung tapioka terhadap kualitas keripik bakso daging ayam dengan metode penggorengan vakum (Faculty of Animal Science, Universitas Brawijaya, 2011)
ABSTRACT: This research was purposed to find out the effect of difference concentration of tapioca starch on quality chicken meatball chips with vacuum frying method based on chemical qualities (water content, water activities/Aw, protein and fat content), physical quality (breaking force and brightness) and organoleptic properties (color, taste and crispness). The result showed that addition of tapioca gives a significant effect (P<0.05) on water content, Aw, taste and crispness, whereas protein, fat content, breaking force and brightness of chicken meatball chips very significant effect (P<0.01), but didn’t gave significant effect (P>0.05) on color. The best result was chicken meatball chips made with used of tapioca 30%, It has water content 4.16%;, Aw 0.42, protein 33.06% and fat content 31,39%; breaking force 5.43 N; brightness 51.3; color 6.64; taste 6.94; and crispness 6.74. The conclusion of this research was addition of tapioca in chicken meatball chips decreased water content, Aw, protein content, breaking force and increased fat content, brigtness and organoleptikproperties. The optimum addition of tapioca on chicken meatball chips were 30%. Keywords: tapioca, chicken meatballs chips, chemical qualities.